Perancangan Ilustrasi Wood Painting dengan Konsep Identitas Bali bersama Enyo Studio - Dharma Wijaya, Anak Agung Bagus; Indira, Wahyu; Bayu Artha, I Gede Agus Indram (AMARASI: JURNAL DESAIN KOMUNIKASI VISUAL, 2024)
Enyo Studio is a creative company active in the field of illustration and design, pioneered by Putu Windu Sucipta A.Md Par., S.Par since 2019. Enyo Studio in its development has several business lines such as Zaloukh Apparel, Wall Painter, and Triple Eight Gallery. One of the typical merchandise forms of Enyo Studio is wood painting. In this study, the author will raise the characteristic characteristics of the Enyo Studio as the title of the report, namely about the Wood Painting Illustration Design with the Bali Identity Concept with Enyo Studios. The aim of this research is to understand the management process of artwork at Enyo Studio, and to know the process of creation of illustrations of wood painting with the concept of Bali identity in Enyo Studios. There are several methods of data collection in this study, including observation methods, interviews, library studies, and documentation. The data analysis technique used is a descriptive technique. The results of the analysis showed that wood painting became a common artwork and was routinely produced in the Enyo Studio for further promotion by the Triple Eight Gallery. In this project, the author designed a series of wood painting about the Bali culture that is embodied in the theme and major work of “Undagi Bali”. The design of the illustration includes the stage of sketch, contour/outline, stages of coloring and finishing, as well as mockup and application on hardboard media. In addition, the wood painting series was created to meet the SKS capacity of the author's main work in designing illustrations of wood paintings with Bali identity concepts, including the series "Woman Prayer", series "Terasering Bali", Series "Cewek Ngusung Gebogan", and series "Pura Bali".